1997
DOI: 10.1001/archpsyc.1997.01830150070011
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Measurement of Cerebral Metabolic Correlates of Yohimbine Administration in Combat-Related Posttraumatic Stress Disorder

Abstract: These findings are consistent with our previous hypothesis of enhanced norepinephrine release in the brain with yohimbine in patients with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
154
2
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(170 citation statements)
references
References 80 publications
9
154
2
5
Order By: Relevance
“…Moreover, the reduction and increase of noradrenergic activity attenuated and precipitated, respectively, some of the symptoms in PTSD patients (Boehnlein and Kinzie, 2007;Bremner et al, 1997;Raskind et al, 2007;Southwick et al, 1993;Taylor et al, 2008). Evidence of noradrenaline dysregulation have been also shown in several studies measuring noradrenaline in the urinary system and in plasma of PTSD patients (reviewed in (Strawn and Geracioti, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, the reduction and increase of noradrenergic activity attenuated and precipitated, respectively, some of the symptoms in PTSD patients (Boehnlein and Kinzie, 2007;Bremner et al, 1997;Raskind et al, 2007;Southwick et al, 1993;Taylor et al, 2008). Evidence of noradrenaline dysregulation have been also shown in several studies measuring noradrenaline in the urinary system and in plasma of PTSD patients (reviewed in (Strawn and Geracioti, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…It has been proposed that an altered noradrenergic activity may contribute to the hyperarousal symptoms associated with PTSD (Krystal and Neumeister, 2009;O'Donnell et al, 2004;Southwick et al, 1999;Strawn and Geracioti, 2008). This proposal is based on studies showing that the reduction and increase of noradrenergic activity attenuated and precipitated, respectively, some of the symptoms in PTSD patients (Boehnlein and Kinzie, 2007;Bremner et al, 1997;Raskind et al, 2007;Southwick et al, 1993;Taylor et al, 2008). Additionally, the systemic treatment with pharmacological agents that reduce noradrenergic transmission normalized acoustic startle response in mice previously exposed to inescapable foot-shock (IFS) (Olson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44] Across these studies, however, dysfunctional alterations occurred in different parts of the prefrontal cortex, indicating that failure of prefrontal inhibition in PTSD needs to be clarified in the future. In the present study, a reduction of GABA A -benzodiazepine BP throughout the frontal cortex was found.…”
Section: Discussionmentioning
confidence: 90%
“…Other PET trials found that, compared with controls, PTSD subjects show reduced blood flow in the middle temporal gyrus when applying symptom-provoking tasks (traumatic pictures, sounds, trauma-related psychological images and administration of yohimbine) [28,50,51] . The middle temporal gyrus can inhibit the function of the amygdala, facilitate the extinction of fear conditioning [52,53] , and is linked to episodic memory as well as language processing [54] .…”
Section: Discussionmentioning
confidence: 99%